Implementation of the Application of Islamic Business Ethics in Increasing Customer Satisfaction and Business Sustainability - Nuraprila, Shintia; Haris, Ibnu; Mulyono, Sri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze how Islamic business ethics are applied to the Lancar Jaya duck egg business and its impact on customer satisfaction and business sustainability. The research method will use a qualitative descriptive approach that utilizes interview and observation techniques. This research shows that the application of the principles of Islamic business ethics in the form of honesty, trust, fairness, and responsibility in daily business practices will positively impact customer satisfaction and business sustainability. These principles are applied in various operational aspects, from production to marketing, which include providing accurate information, maintaining product quality, and establishing good relationships with business partners. This study confirms that Islamic business ethics are important from a moral perspective and an effective business strategy. For sustainability, it is recommended that the Lancar Jaya duck egg business continue to integrate the principles of Islamic business ethics, improve communication with consumers and business partners, and optimize product quality and employee training.